Digital Twin and Manufacturing Simulation Integrated Platform embedded in cyber-physical system. Issue 1 (July 2021) - Leng, Bohan; Sun, He; Si, Guojin; Xia, Tangbin; Wang, Hao
Abstract: Simulation on manufacturing process of production line is essential to reduce the cost and time of production line layout design. Traditional simulation methods either have low fidelity or depend on actual equipment and external tools. Digital Twin is a core element in Industry 4.0 and is viewed as the next generation of simulation. However, applying Digital Twin to simulate manufacturing process is inadequately researched. To simulate and assess the manufacturing process of production lines in advance, this paper proposes Digital Twin and Manufacturing Simulation Integrated Platform (DTMSIP) embedded in Cyber-Physical System (CPS). Powered by the Plug-and-Play CPS, DTMSIP can serve the function of both monitoring and simulation, where fidelity is ensured by precise mapping of Digital Twin. After DTMSIP is established for a reconfigurable production line, DTMSIP as a simulation method is validated on a reconfiguration evaluation problem in this paper.